Whole-Genome Sequencing-Based Antimicrobial Resistance Characterization and Phylogenomic Investigation of 19 MultidrugResistant and Extended-Spectrum Beta-Lactamase-Positive Escherichia coli Strains Collected From Hospital Patients in Benin in 201 - Yehouenou, Carine Laurence; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; Bogaerts, Bert; De Keersmaecker, Sigrid C. J.; Roosens, Nancy H. C.; Marchal, Kathleen; tchiakpe, nicole; AFFOLABI, DISSOU (My University, 2021)
The increasing worldwide prevalence of extended-spectrum beta-lactamase (ESBL) producing Escherichia coli constitutes a serious threat to global public health. Surgical site infections are associated with high morbidity and mortality rates in developing countries, fueled by the limited availability of effective antibiotics. We used whole-genome sequencing (WGS) to evaluate antimicrobial resistance and the phylogenomic relationships of 19 ESBL-positive E. coli isolates collected from surgical site infections in patients across public hospitals in Benin in 2019. Isolates were identi"ed by MALDI-TOF mass spectrometry and phenotypically tested for susceptibility to 16 antibiotics. Core-genome multi-locus sequence typing and single-nucleotide polymorphism-based phylogenomic methods were used to investigate the relatedness between samples. The broader phylogenetic context was characterized through the inclusion of publicly available genome data. Among the 19 isolates, 13 different sequence types (STs) were observed, including ST131 (n=2),
Keywords: Escherichia coli; whole-genome sequencing; extended-spectrum beta-lactamases; antimicrobial; resistance; Benin